Correctional Officers’ Perceptions about the Safety and Control of Prohibited Items Entering into Prisons and Penitentiaries - Tititampruk, Dittita; Ketsil, Tanet (International Journal of Criminology and Sociology, 2021)
The smuggling of prohibited items is one of the significant problems faced by prisons worldwide. This research explores the smuggling of prohibited items into Thai prisons by examining the perceptions of 20 correctional officers, who are directly involved in the prevention and suppression of such issues, by using qualitative research techniques. The results reveal that although measures have been put in place to prevent the smuggling of prohibited items and avert any prison searches, there are still channels for smuggling items in medium and maximum-security prisons. Finally, how other strategies may be employed by correctional administrators to control their facilities and environments are discussed.